2018
DOI: 10.1016/j.jsp.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in response to a school-based mindfulness training intervention for early adolescents

Abstract: Mindfulness training has been used to improve emotional wellbeing in early adolescents. However, little is known about treatment outcome moderators, or individual differences that may differentially impact responses to treatment. The current study focused on gender as a potential moderator for affective outcomes in response to school-based mindfulness training. Sixth grade students (N = 100) were randomly assigned to either the six weeks of mindfulness meditation or the active control group as part of a histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 103 publications
(127 reference statements)
9
55
0
2
Order By: Relevance
“…Furthermore, it must be acknowledged that the current study involved an all-female sample, and therefore it is unknown to what extent the aforementioned considerations generalize to males. Given the recent proliferation of studies highlighting gender differences in mindfulness research [77][78][79]149 , including the very pertinent finding that males are underrepresented in mindfulness studies 150 , we strongly encourage future replication efforts with a large balanced sample.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it must be acknowledged that the current study involved an all-female sample, and therefore it is unknown to what extent the aforementioned considerations generalize to males. Given the recent proliferation of studies highlighting gender differences in mindfulness research [77][78][79]149 , including the very pertinent finding that males are underrepresented in mindfulness studies 150 , we strongly encourage future replication efforts with a large balanced sample.…”
Section: Resultsmentioning
confidence: 99%
“…Additional programs to address mental wellness, possibly through school-based mindfulness interventions, can supplement China’s cash-transfer social welfare programs. School-based mindfulness trainings have shown strong positive effects on the emotional well-being of adolescent students [ 77 , 78 ]. In one study, the mindfulness intervention group reported significant decreases on rumination, intrusive thoughts, and emotional arousal [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown gender differences in response to a school-based mindfulness intervention. A recent study by Kang et al (2018) indicates that female six-graders benefited more from a school-based mindful intervention compared to male sixgraders. As for ethnicity differences in response to our intervention, it is possible that bilingual (English and Spanish) take-home activity kits that included an activity card, a recipe, and/or nonperishable items were effective in promoting mindful eating practices among Hispanic families.…”
Section: Discussionmentioning
confidence: 99%